PER VS PBV: STRATEGY TO FIND FAIR PRICES FOR TLKM, ISAT, AND EXCL SHARES (2019–2023) - Amin, Aminul; Salim, Agus (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
This study aims to assess the fair value of shares in the telecommunications sector listed on the Indonesia Stock Exchange, specifically PT Telekomunikasi Indonesia Tbk (TLKM), PT Indosat Tbk (ISAT), and PT XL Axiata Tbk (EXCL) during the 2019–2023 period, using two valuation approaches: Price Earning Ratio (PER) and Price to Book Value (PBV). The PER method evaluates stocks based on company profitability through earnings per share (EPS), while the PBV method assesses stocks based on the company's asset value. The research findings indicate varying stock valuation conditions depending on the chosen approach, where undervalued stocks potentially offer promising returns if market prices move closer to their intrinsic values. These findings suggest that combining PER and PBV methods provides a more comprehensive valuation analysis to support investment decision-making. The study recommends that investors consider both ratios in evaluating stock investment feasibility.